Cognitive mediation in people with dementia: Development, structural, and construct validity of the first dementia‐specific measure. (19th July 2019) - Stott, Joshua; Cadman, Tim; Scior, Katrina; Brede, Janina; Chadwick, Eleanor; Charlesworth, Georgina
Abstract : Objectives: Anxiety and depression are common and deleterious comorbidities in people living with dementia (PLWD). Cognitive behavioural therapy (CBT) is one of the few promising treatments; however, it is unclear whether PLWD have the necessary prerequisites to engage in this. Having an understanding of cognitive mediation, that a thought mediates the relationship between an antecedent event and its emotional consequence, is key for engaging with CBT and is also a critical component of emotion regulation. There are no measures of this construct validated for PLWD. This study aims to adapt and validate an existing measure for this population. A secondary aim is to assess its applicability in older adults (OA) without a recognised neurocognitive impairment. Methods: A measure of cognitive mediation was adapted via expert and service user consultation for use in PLWD. A total of 102 PLWD and 77 OA without neurocognitive impairments completed the adapted measure along with two measures of emotion recognition and reasoning. Factor structure was examined separately in both samples, and the measure reduced, with convergent validity assessed. Results: A final measure of 10 items (named the CM‐Dem) was subject to factor analysis yielding a single factor solution. The measure showed good psychometric properties in PLWD, including good model fit, high internal consistency, inter‐rater reliability, and moderate convergent validity with related constructs. In contrast, poor validity was found in OA, especially a lack of convergent validity. Conclusions: The CM‐Dem has clinical and research utility as a measure of cognitive mediation in PLWD, but less so in OA.